Pemberdayaan Masyarakat Melalui Inovasi Biji Kopi Sajang Rinjani untuk Meningkatkan Nilai Tambah Produk Berbasis Model Ekonomi Sirkular - Rengganis, Baiq Santi; Fathurrahman, Fathurrahman; Novida, Sari (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to improve the knowledge and skills of partners in upgrading coffee beans to increase the added value of products based on a circular economy model. This community service activity was carried out in Sajang Village, East Lombok Regency using the participatory action research (PAR) method which is oriented towards community empowerment through training and socialization. The evaluation instrument for this activity used a questionnaire and was analyzed descriptively. The results of this service show that partners have been able to improve products from coffee beans to ground coffee with the addition of vanilla and organic cloves. In addition, partners have the ability to design packaging and financial literacy to record product marketing input-output, and can make compost from chopped coffee grounds.